Bioestimulantes e condicionadores de solo no cultivo de Physalis peruviana - Oliveira, Henrique Martins de (2017)
The cultivation of Physalis peruviana, family solanaceae, widely known in Colombia and native from the South American Andes, is still little explored in Brazil. It is a new diversification option for small producers, with good prospects for the national and international market. Seaweed extracts and soil conditioners have improved crop performance and are an eco-friendly alternative to fertilizer use. The objective was to evaluate the use of soil biostimulants and conditioners in the cultivation of physalis. The experiment was conducted in the greenhouse, with irrigation system, in the Vegetable farming Sector of the Federal University of Lavras, between May and October, 2016. Seedlings were planted in 20-liter pots with Tropstrato commercial substrate along with soil conditioners (Limestone of oyster shells and Lithothamnium calcareum) at the concentration of 6kg.m-3 . Each 15 days, they were pulverized via foliaceous with algae extract biostimulants (Treatment A-Seaweed Ascophyllum; Treatment B-Algae Laminaria digitata and Hypnea musciformis; Treatment C -Algae Laminaria digitata; Hypnea musciformis and Sargassum Vulgare) at the concentration of 10mL.L -1 . The experimental design was completely randomized, in factorial 2 x 3 (2 soil conditioners x 3 algae extracts), with 6 treatments, with 18 replications. Statistical analysis used Poisson distribution model, a generalized mixed model that expresses the probability of a series of events occurring in a certain period of time. Phytotechnical analyzes were carried out, measuring plant height, number of flowers, number of fruits, fruit diameter, stem diameter, chlorophyll content and yield per plant. The plants were tutored in bamboo of 1.80 meters, tied with tape. Thus, two conditioners and the three combinations of algae were efficient in the increments and production of Physalis peruviana.